STUDY OF FUNCTIONAL LATERALIZATION IN NIGERIAN ADULTS - RAYYANU Z. S; MURTALAM.J.; ASALA A.S (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
The aim of the present study is to assess the incidence of functional lateralization in Nigerian adult residing in Maiduguri. A total number of 200 normal and healthy adult individuals were randomly selected for the study, in which 115 were males and 85 were females. The data was collected through self – assessment questionnaires, which consist of 14 questions on the tasks of handedness, 4 tasks on footedness 1 task on ear and 1 task for chewing. The test for functional lateralization was carried out by chi – square test using SPSS version 18.0 software (IBM Corporation, USA). The result shows that there is no significant difference for the right and left sidedness between males and females sexes with P = 0.6894 for right side in males against right side in female and p = 0.092 for left side in males against left side in females, but the right sidedness is significantly greater than left sidedness in both males and females sexes with P<0.0001, in which for the handedness 84% prefer right, 11% prefer left and 5% prefer both, for footedness 75% prefer right, 17% prefer left and 8% prefer both, for hearing 74% prefer right, 16% prefer left and 10% prefer both, for chewing 62% prefer right, 17% prefer left and 21% prefer both. This study finds out that in every population 99% of them may be right sidedness and 1% of them may be left sidedness, this shows that the left cerebral hemisphere more dominant than right cerebral hemisphere.